Exploring The Ethical Governance of Artificial Intelligence from An Islamic Ethical Perspective - Kannike, Uthman Mohammed Mustapha; Fahm, AbdulGafar Olawale (Jurnal Fiqh, 2025)
This study aims to examine the intersection of contemporary artificial intelligence (AI) with Islamic ethics, specifically exploring how foundational Islamic ethical principles can guide the integration and governance of AI technologies. Employing a theoretical and conceptual analysis method, the research investigates epistemological and theological considerations related to the application of machine learning algorithms in interpreting sacred Islamic texts. The core theoretical underpinnings guiding this analysis include Tawḥīd (the Oneness of God), which emphasizes harmony and ethical coherence; Maqāṣid al-Sharīʿah (Objectives of Islamic Law), focusing on safeguarding fundamental human interests such as faith, life, intellect, progeny, and wealth; Ihsan (Excellence and Benevolence), advocating for moral excellence in technological applications; and ʿAdl (Justice), which demands equity and fairness in technological advancements. The findings indicate that while AI holds significant promise for enhancing societal welfare, education, healthcare, and economic justice within Muslim communities, it presents profound ethical challenges, including algorithmic bias, privacy infringement, human autonomy erosion, and accountability concerns. The study highlights the necessity of rigorous ethical oversight grounded in Islamic ethics to navigate these challenges, proposing that AI applications adhere to principles of justice, transparency, and the preservation of human dignity and autonomy. The implications of this research extend beyond theoretical considerations, underscoring the importance of interdisciplinary collaboration between Islamic scholars, ethicists, policymakers, and technologists. Islamic ethical guidelines can enrich global conversations on AI ethics, ensuring technological innovations align with universally recognized moral standards while promoting social justice and human flourishing.